Grade 11 rural teachers’ perceptions of and the teaching of Sepedi literature and English literature in Acornhoek, Mpumalanga Province: A critical study - Mafunganyika-Ndlovu, Annie Tiny (University of the Witwatersrand, Johannesburg, 2024)
This study investigated the intricate relationship between language, culture, and knowledge within the context of rural South African high schools. It emphasised the pivotal role of language as both a cultural carrier and a determiner of which knowledge is valued or overlooked. Central to this exploration is the impact of literature teaching, especially in African languages, serving as a reflective mirror of society, history, and individual experiences over time. As part of a broader research project titled “Conditions of Teaching and Learning that Facilitate and/or Constrain Learning English in Rural High Schools,” this study focused on the teaching of Sepedi language literature and English literature in Acornhoek secondary schools. It aimed to reveal how literature teaching can renegotiate and articulate the complexities of rural epistemological repositories, values, moral wisdom, and social cohesion. By examining the pedagogical approaches of grade 11 teachers towards Sepedi language literature and English literature, the study sought to identify underlying assumptions that influenced their teaching methods. Utilising cultural historical activity theory (CHAT) and Bernstein’s concepts of visible and invisible pedagogy, the research conducted a deep dive into teachers’ responses, discourses, and classroom practices. This theoretical backdrop facilitated an understanding of literature’s pedagogy, underscoring the significance of reflective teaching and literature’s potential as a tool for social justice and cultural affirmation. The study engaged with four teachers across four secondary schools in Acornhoek, Mpumalanga Province, employing qualitative non- participatory observation, video-stimulated recall interviews, and semi-structured interviews to gain insights into teachers’ pedagogical choices and perceptions. This multi-faceted approach allowed for an in-depth analysis of teaching practices, encouraging teachers to become more aware of their methodologies with the goal of enhancing the educational experience and deepening the understanding of literature’s societal and educational roles. Findings from the study, analysed through Scott and Mortimer’s Communicative Approach, highlighted the complexity of teaching, though there was dominance of teacher-centered interpretations of literature. This overshadowed opportunities for learners’ active participation to learning and meaning making, because teachers leant the literature for the learners. Despite occasional use of dialogic teaching methods, these instances were sporadic v and largely implicit. The research further identified several challenges, including limited resources, teachers’ perceptions of their learners, and time constraints, as key factors prompting authoritative teaching practices. Based on these insights, the study recommends further research that will include learners to get the overall teaching and learning picture in rural classrooms, to better understand the evolving pedagogies and learning approaches. Also to expand research into investigating the diversity that exists within African indigenous languages.
A research report submitted in fulfillment of the requirements for a Doctor of Philosophy, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; rural teachers; Grade 11; Sepedi literature; English literature; Mpumalanga Province; SDG-4: Quality education